Ion transport property, structural features, and applications of cellulose-based nanofluidic platforms — A review. (1st August 2022) - Sun, Zhe; Ahmad, Mehraj; Wang, Sha
Abstract: Mimicking the cellular machineries-based ion transport phenomenon for multipurpose applications of the nanofluidic devices has inspired scientific community. Owing to this phenomenon, various artificial nanofluidic systems are highly desirable for energy-environment associated fields including energy storage and conversion, biosensing, and desalination of seawater. Nevertheless, high cost and low efficiency hamper the development of nanofluidic devices in the respective fields. Pertinently, cellulose-based nanofluidic devices rectified the ionic transport property and offer an efficient and sustainable platform for harvesting osmotic energy. Recently, the design strategies of cellulose-based nanofluidic materials provided a more targeted material design for specific applications. Herein, we briefly introduce the structural aspects of cellulose, review the structural features and ion transport properties of cellulose-based nanofluidic materials, and highlight their applications as osmotic energy generators, sensors, transistors, flexible electronic skins, and bio-detection devices. In summary, the challenges and future perspectives of cellulose-based nanofluidic materials are described. Graphical abstract: Unlabelled Image